Rozprzestrzenianie się fal w sprężystym ortotropowym walcu kołowym - Kozarow, M.; Iwanow, TS. P. (Engineering Transactions, 1969)
In the following article the propagation of elastic waves of the type (1.1) in an infinite orthotropic circular cylinder is investigated. That is the most-general case of cylindrical anisotropy, for which the propagation of waves of this type is possible. The solutions of the unknown functions U(r), V(r), W(r) are determined in the form of generalized power series, convergent for every r = 0. For some meanings for the elastic constants by given v it is possbile to receive solutions, having logarithmic singularities for r = 0, The boundary conditions the cylindrical surface to be free from loading, can always be satisfied for a hollow cylinder, whereas by a solid cylinder that is possible only for some orthotropic materials, for which the elastic constants satisfy some additional inequalities, depending on v. Determined are the cases. frequency equations in the general case as well as some interesting particular.